2011
DOI: 10.1111/j.2044-8341.2011.02040.x
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating spirituality in psychosocial group intervention for women undergoingin vitrofertilization: A prospective randomized controlled study

Abstract: These findings suggest that I-BMS intervention was successful at improving the psychosocial and spiritual well-being of women undergoing their first IVF treatment cycle. This study highlights the importance of providing integrative fertility treatment that incorporates psychosocial and spiritual dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 35 publications
2
80
0
1
Order By: Relevance
“…Of the seven interventional studies included, six adopted a randomized controlled trial (RCT) design in which the participants were randomly assigned to an intervention group receiving psychosocial interventions or to a control group with usual care provided (Lee , Chan et al . , , Abedinia et al . , Mosalanejad et al .…”
Section: Resultsmentioning
confidence: 99%
“…Of the seven interventional studies included, six adopted a randomized controlled trial (RCT) design in which the participants were randomly assigned to an intervention group receiving psychosocial interventions or to a control group with usual care provided (Lee , Chan et al . , , Abedinia et al . , Mosalanejad et al .…”
Section: Resultsmentioning
confidence: 99%
“…A variety of psychosocial interventions, such as cognitive behavioural therapy [9][10][11], mind body intervention [12][13][14], counselling [15][16][17][18] and positive reappraisal coping therapy [19,20], have been adopted to improve the mental health, pregnancy rates and marital function of couples who undergo IVF treatment. However, in a review of the literature, the effects of relevant interventions tested in randomized controlled trial studies could not be confirmed due to methodological or practical issues [21].…”
Section: Introductionmentioning
confidence: 99%
“…These investigators also suggest that women may benefit more from psychological interventions when compared with their male partners. Recently, the Integrative Body-Mind-Spirit intervention has proved successful at improving the psychosocial and spiritual well-being of women undergoing their first IVF treatment cycle (16). Domar and colleagues examined the impact of a group mind/body intervention on pregnancy rates in IVF patients and found that participation in such a program increased pregnancy rates for cycle 2, but mental health variables were not studied (17).…”
mentioning
confidence: 99%